TRADISI SEDEKAH LAUT DI MASYARAKAT NELAYAN DESA ANGKUE KECAMATAN KAJUARA KABUPATEN BONE - Iis Damayanti ,; Mubarak dahlan .; Firdaus W Suhaeb (ALLIRI Journal of Anthropology, 2022)
ABSTRACT This study aims (1) to determine the background of the implementation of sea alms in Angkue Village, Kajuara District, Bone Regency. (2) to find out the stages of implementing sea alms in the fishing community of Angkue Village, Kajuara District, Bone Regency. (3) to find out the function of the implementation of sea alms in the fishing community of Angkue Village, Kajuara District, Bone Regency. In this study, the researcher used qualitative research methods which were analyzed and written descriptively. While the informants selected were from among traditional stakeholders, traditional leaders, the Ankue village community who had held and or participated in sea alms tradition activities, the researchers then collected data by conducting observations, interviews and collecting documentation. The results showed that: (1) The sea alms tradition is one of the traditions that is still carried out and maintained, preserved by the fishing community in Angkue village. The sea alms tradition is carried out by fishermen who are just going to sea again after a long periond of not being used or boats that have been renoveted and usually done by fishermen before going to sea, where the boat or bagang they use first performs the sea alms tradition which the Bugis people usually call the mappasoro tradition.(2) In the sea alms tradition, the fishing community must prepare the offerings needed in the implementation of the sea alms tradition. After the preparations are complete, all the families go to the river and bring offerings that will be handed over to the river, before the prayer is read by the sanro (Shaman) they prepare offerings, incense and incense which contains charcoal wood, san kemenyang is burned on coals. Then the offerings are handed over on the beach with a prayer read by the sanro (shaman). (3) the sea alms tradition is a form of gratitude to God Almighty. Because the fishermen get.